Formation à distance et activité du stagiaire de la formation professionnelle continue - Béatrice Verquin-Savarieau (Éducation et Socialisation)
This paper discusses the practical vocational training in the framework of a hybrid system. This is particularly ask the vocationnal education training as operational content to facilitate the transformation of subjects in action. We present the crucial role played by the engagement letter, as a tool for adjustment and regulation to the expectations of the university. The methodology presented is in analytical engineering training approaches, built from reading four business areas. Analysis of the activities is not a device in this type of training, but allows us to question the design of the training.